(untitled) (World Science, 2019)
The article is devoted to the issues of cooperation of Uzbekistan with UN human rights bodies in the field of women’s rights. The author considers issues of cooperation with the UN human rights treaty bodies, subsidiary bodies and specialized agencies, as well as with special UN rapporteurs and programs on ensuring and protecting human rights. The article highlights the main directions and forms of cooperation in this direction. An overview of the recommendations of these structures regarding Uzbekistan and the results of cooperation is given.